Some new recorded species for the family Gracilariaceae (Rhodophyta) for the algae of Vietnam - Hau, Le Nhu (Academia Journal of Biology, 2012)
On the basis of the taxonomic criteria utilized in the family (Gracilariaceae) which was presented by Abbott et al. (1985): species identification must be based on the difference of gross morphology and combinated with reproductive anatomical details as spermatangial conceptacles, cystocarps, the presence of nutritive filaments, the shapes of cells that make up the pericarps. After re-examination of more than 600 specimens of Gracilariaceae previously collected by the others and newly collected by author along the coast of Vietnam, which are deposited in the herbarium at the Institute of Oceanography Nhatrang (ION), Nhatrang Institute of Technology Research and Application (NITRA) and Institute of Marine Environment and Resource Haiphong (IMER), There were 20 species identified for Vietnamese Gracilariaceae, of those, five species are new records for the red alga of Vietnam, namely Gracilaria cuneifolia (Okamura) Lee & Kurogi, Gracilaria rubra Chang & Xia, Gracilaria yamamotoi Zhang & Xia, Hydropuntia divergens (Xia & Abbott) Wynne, Gracilariopsis nhatrangensis Le & Lin. Nomenclature, distribution, biology and ecology of all species were also provided.